Pharmacological treatments of neuropathic pain: The latest recommendations - Attal, N. (Revue neurologique, 2019)
We provide an up-to-date review of the pharmacological treatment of neuropathic pain with emphasis on the latest evidence-based recommendations for its pharmacological treatment. Drugs proposed as first line include tricyclic antidepressants (particularly amitriptyline), serotonin–norepinephrine reuptake inhibitors (particularly duloxetine), pregabalin and gabapentin. Second line treatments include lidocaine plasters and capsaicin high concentration patches for peripheral neuropathic pain only, and tramadol. Third line treatments include strong opioids and botulinum toxin A (for peripheral neuropathic pain). Perspectives include the development of new compounds and a more personalized therapeutic approach, which is made possible by recent progress in the assessment and understanding of neuropathic pain.